Association between employee department and responsible gambling program perceptions. Issue 3 (2nd September 2019) - Abarbanel, Brett; Gray, Heather M.; LaPlante, Debi A.; Bernhard, Bo J.
ABSTRACT: Academic studies of employee perceptions of and engagement with responsible gambling (RG) provide important insight into how employees engage with RG, but typically treat employees as a singular entity. Employees in different departments, however, have different work experiences that affect their likelihood of directly interacting with gamblers. It is conceivable that degree of contact with gamblers affects employees' opinions about RG. To examine this possibility, we surveyed cohorts of employees at MGM Resorts International (MGM) (N = 2, 192) regarding their (1) perceptions of RG programs, (2) behaviors and beliefs about gambling, and (3) comfort with MGM's corporate RG environment. Using MANCOVA, with years employed in the gambling industry as a covariate, we observed that employees in departments with less direct contact with gamblers were more likely to perceive RG programs to be effective at MGM than employees who have more direct contact with gamblers. In addition, employees who work in the Food, Beverage, & Retail departments were more likely to hold misconceptions about gambling than employees in Back of House operations. The differences in how departments view RG programs suggest that one-size-fits-all approaches to employee training might not be suitable for RG topics, and that position-based training might be necessary.